2015
DOI: 10.1021/acs.est.5b01711
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Environmental Toxicity of Silver Nanoparticles through Shape Control

Abstract: The use of antibacterial silver nanomaterials in consumer products ranging from textiles to toys has given rise to concerns over their environmental toxicity. These materials, primarily nanoparticles, have been shown to be toxic to a wide range of organisms; thus methods and materials that reduce their environmental toxicity while retaining their useful antibacterial properties can potentially solve this problem. Here we demonstrate that silver nanocubes display a lower toxicity toward the model plant species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 30 publications
3
64
1
Order By: Relevance
“…Notebly, considering the different sizes, morphologies of NPs and differents plants species, the acquisition strategies of Fe elements as the nanoparticulates may not always effective [14]. In our study, Fe 2 O 3 NCs and Fe 2 O 3 SRs had no obvious effect on germination, but Fe 2 O 3 LRs inhibited this crucial index siginificantly.These interesting phenomenon seems can be largely due to the nanomaterials' morphologies.Recently it was reported that AgNPs have higher toxicity than AgNCs and AgNWs, which indicated the influence of nanomaterials on plants [15]. Xiang et.al found that ZnO hexagonal nanorod and ZnO nanocolumniation showed different bio-effect to Chinese cabbage seeds [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notebly, considering the different sizes, morphologies of NPs and differents plants species, the acquisition strategies of Fe elements as the nanoparticulates may not always effective [14]. In our study, Fe 2 O 3 NCs and Fe 2 O 3 SRs had no obvious effect on germination, but Fe 2 O 3 LRs inhibited this crucial index siginificantly.These interesting phenomenon seems can be largely due to the nanomaterials' morphologies.Recently it was reported that AgNPs have higher toxicity than AgNCs and AgNWs, which indicated the influence of nanomaterials on plants [15]. Xiang et.al found that ZnO hexagonal nanorod and ZnO nanocolumniation showed different bio-effect to Chinese cabbage seeds [16].…”
Section: Discussionmentioning
confidence: 99%
“…Xiang et.al found that ZnO hexagonal nanorod and ZnO nanocolumniation showed different bio-effect to Chinese cabbage seeds [16]. Different morphologies may affect dissolution, uptake, stability of nanomaterials [15], result into gene expression alteration [17], further affect plants growth. Our study demonstrated that Fe 2 O 3 long nanorods had higher toxicity on germination than Fe 2 O 3 nanocubes and Fe 2 O 3 short nanorods, but the machanism need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the safety issue that could arise from industrial use of nanomaterial-based conductors should be addressed. There are ongoing studies on the toxicity of the nanomaterials themselves [233][234][235][236] and potential exposure to nanomaterials as a result of them being released from products has been very recently investigated. [187] STICs can be promising candidates because most of the hydrogels are biocompatible and are conformal to human body parts, cells, and tissues down to the molecular scale.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…As a result, a wide spectrum of metallic and bimetallic nanoparticles, including Ag, Au, Fe, Co, Pt, Fe-Pt, and Au-Pd, have been extensively produced during the last two decades using this polyol technique. [3][4][5][6][7][8] In addition to ethylene glycol, low-molecular-weight polyethylene glycol melts (200-600 g mol À1 ) were also found to have the capacity to form silver nanoparticles.…”
Section: Introductionmentioning
confidence: 99%